2023
DOI: 10.3390/bioengineering10050545
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Three Facial Scanners for Creating Digital Twins by Focusing on the Difference in Scanning Method

Abstract: Background: Multi-dimensional facial imaging is increasingly used in hospital clinics. A digital twin of the face can be created by reconstructing three-dimensional (3D) facial images using facial scanners. Therefore, the reliability, strengths, and weaknesses of scanners should be investigated and approved; Methods: Images obtained from three facial scanners (RayFace, MegaGen, and Artec Eva) were compared with cone-beam computed tomography images as the standard. Surface discrepancies were measured and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…They use active light projections to render complex geometry, sharp corners and edges and other morphological characteristics for 3D images or models production of the object being scanned [70]. With the features of low cost, portability, surface texture captions, and reproducibility, surface scanning manifests its application feasibility in the skull [71] and pelvis [60] reconstructions which lay the foundation for its application to sex estimation. Despite the fact that relevant studies [57][58][59] on 3D surface scanning of skulls do not reflect its specific application to sex estimation, its strong metric analysis ability and high reproducibility advocate a high potential of this method to serve as an optional method for sex estimation based on skull structure when the complex CT imaging facility is not available.…”
Section: Discussionmentioning
confidence: 99%
“…They use active light projections to render complex geometry, sharp corners and edges and other morphological characteristics for 3D images or models production of the object being scanned [70]. With the features of low cost, portability, surface texture captions, and reproducibility, surface scanning manifests its application feasibility in the skull [71] and pelvis [60] reconstructions which lay the foundation for its application to sex estimation. Despite the fact that relevant studies [57][58][59] on 3D surface scanning of skulls do not reflect its specific application to sex estimation, its strong metric analysis ability and high reproducibility advocate a high potential of this method to serve as an optional method for sex estimation based on skull structure when the complex CT imaging facility is not available.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive analytics offered by the software have been carefully linked with the actual treatment plan, allowing for easy monitoring and strict adherence to the devised treatment plan. The scanning accuracy of the RAYFace for creating digital face twins has been reported to be good, with an absolute surface discrepancy of 0.5277 when compared with the MegaGen and Artec Eva systems [94]. By integrating facial scans with CBCT, another study found RAYFace to be useful in identifying true mid-sagittal planes and anatomical landmarks [95].…”
Section: Rayfacementioning
confidence: 99%
“…The Azure Kinect development kit (Azure Kinect DK, Microsoft Inc., Redmond, WA, USA), released in 2020, is based on a continuous-wave time of flight (ToF) camera and seems to be a viable 3D scanning solution for clinical and research applications, with a systematic error of less than 2 mm [34,35]. The RAYFace (RayMedical, Ray Co., Ltd., Seongnam, Republic of Korea) is a 3D one-shot face-scanning solution developed in 2020 and reached an absolute surface discrepancy of 0.5277 when compared with other facial scanners [36]. Regarding the Intel 3D camera D435 (Intel Corporation, Santa Clara, CA, USA), one of the most popular RGBD sensors, Singh et al [33] report that there is little research on its reliability.…”
Section: Introductionmentioning
confidence: 99%